Capital Structure Determinants in Technology vs. Non-Technology Firms on the Indonesia Stock Exchange - Irwan Moridu; Nurcahya Hartaty Posumah; Fitriani (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Rapid digitalization has fundamentally transformed business models, investment patterns, and financing decisions, prompting firms to reassess how they structure and manage capital in an increasingly technology-driven environment. This study aims to analyze the determinants of corporate capital structure in the digital era and compare the influence of these factors between technology-based and non-technology companies listed on the Indonesia Stock Exchange. The study uses a quantitative explanatory approach with secondary data from companies’ annual financial reports for the period 2018–2023. The analysis was conducted using multiple regression to examine the influence of each determinant and the differences in patterns between the two groups of companies. The results show that asset tangibility has a significant positive effect on the debt-to-equity ratio in both groups, while profitability has a significant negative effect, consistent with the pecking order theory. Company size is only significant in non-technology companies, while growth and liquidity show different influences between the groups. These findings confirm that the characteristics of the digital industry, particularly the dominance of intangible assets and high capital requirements for innovation, influence capital structure policies differently from traditional industries, providing important empirical insights for financial managers and capital market stakeholders in Indonesia.